Retropharyngeal Abscess: A Case Report - Dadá, Mahomed Sidique Abdul Cadar; Dadá, Abdul Habib Mahomed; Dadá, Zulaikhah Mahomed Sidique; Rodrigues, Jorge Miranda (Brazilian Journal of Case Reports, 2026)
Retropharyngeal abscess is a rare but potentially fatal condition, often misdiagnosed as other respiratory conditions in children due to its nonspecific symptoms. This case highlights the importance of clinical awareness and timely radiological evaluation to ensure early diagnosis and appropriate treatment, preventing severe complications like mediastinitis and ensure effective treatment.